An Attempt to Restore the Ordinary Death to the Visual Realm—Artistic, Therapeutic, and Ethical Aspects of the Post-Mortem Photography of Children in the 21st Century. Short Introduction - Lange, Łucja (Qualitative Sociology Review, 2020)
Post-mortem photography was a transcendental element in the 19th century, which not only democratized portraiture, but also helped in the bereavement process. The comeback of post-mortem photography as a psychological tool helping parents of deceased children to cope with death was only a matter of time. The role and importance of memento-moris has to be taken into account in order to make significant changes in the grieving process, but all of the aspects of this kind of photography need to be considered. The artistic, therapeutic, and ethical dimensions of post-mortem photography in the 21st century has its rules, and those rules need to be followed. The article constitutes only a part of the research devoted to the bereavement process from a sociological perspective.